PENGARUH BIOLOGICAL ASSET INTENSITY, UKURAN PERUSAHAAN, KONSENTRASI KEPEMILIKAN, JENIS KAP, DAN PROFITABILITAS TERHADAP BIOLOGICAL ASSET DISCLOSURE (Pada Perusahaan Agrikultur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Marselina Inggrid Duwu; Sylvia Christina Daat; Hastutie Noor Andrianti (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to obtain empirical evidence on the analysis of factors affecting biological asset disclosure which is still voluntary in the period of this research but has been effective as of January 1, 2018 in agricultural firms in Indonesia. Factors used include biological asset intensity, firm size, ownership concentration, KAP type, and profitability. Measurement of biological asset disclosure using content analysis. There are 40 items to detect the level of biological asset disclosure.Thepopulation of this study is all financial data of agricultural companies listed on the BEI period 2012-2016. Sampling method used in this research is purposive sampling method. The total samples usedin this study were 53 samples. The data used is secondary data from Indonesia Stock Exchange. The analysis technique used is multiple linear regression analysis.The results of this study indicate thatbiological asset intensity and firm size have an effect on biological asset disclosure, while ownership concentration, KAP type, and profitability have no effect on biological asset disclosure